A landscape analysis of psychedelic facilitation training in the US - Roman Palitsky; Caroline Peacock; Jeffrey A. Breau; Paul Gillis-Smith; Gosia Sklodowska (PLoS ONE, 2026)
Skilled interpersonal support and safety monitoring can enhance the therapeutic potential of psychedelic compounds and reduce the potential for harm. In the anticipation of legalized psychedelic care, and the recognition of ongoing psychedelic use across a variety of contexts, numerous training programs have been established to educate psychedelic facilitators in supporting individuals who take psychedelics. However, psychedelic facilitation training in the US has not been well characterized, making it difficult to appraise the strengths, needs, and gaps in this emerging discipline, especially with regard to the development of competencies in spiritually responsive care. This project used a quality improvement approach to identify common priorities, practices, needs, and gaps in the emerging field of psychedelic facilitation training from the standpoint of 13 established and emerging training organizations from the US. Interviews were conducted with one or more representatives from each participating organization. Notes from these interviews, once confirmed by the interviewees, were synthesized to identify common practices, procedures, priorities, and gaps. Areas of focus among the programs included: careful selection of trainees and faculty; content emphases in instruction; addressing spiritual, existential, religious, and theological topics; and teaching strategies used in programs. Several gaps were also identified, pointing to the need for continuing education among program graduates, parity with other disciplines, and development of field standards in training facilitators. Psychedelic facilitation training is an evolving discipline. Training programs and trainees may benefit from greater collaboration, including ongoing exchange about best practices and adjustments to scientific, social, economic, and regulatory developments.